2014
DOI: 10.1002/lary.24830
|View full text |Cite
|
Sign up to set email alerts
|

The utility of common surgical instruments for pediatric adenotonsillectomy

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…21 In comparison, a retrospective chart analysis of 1280 paediatric patients with adenotonsillectomy showed the significantly faster surgical time for monopolar electrocautery versus the PEAK PlasmaBlade™ and radiofrequency ablation and insignificant differences in postoperative haemorrhaging. 22 However, the same study found average overall procedural costs for the PEAK PlasmaBlade™ to be more than eight times as high as for monopolar electrocautery ($30.04 vs $246.95). 22 A randomised controlled trial comparing four different energy-based tissue dissection techniques for abdominoplasty calculated much higher costs for the PEAK PlasmaBlade™, with no significant differences in wound-healing complications and drainage quantity.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…21 In comparison, a retrospective chart analysis of 1280 paediatric patients with adenotonsillectomy showed the significantly faster surgical time for monopolar electrocautery versus the PEAK PlasmaBlade™ and radiofrequency ablation and insignificant differences in postoperative haemorrhaging. 22 However, the same study found average overall procedural costs for the PEAK PlasmaBlade™ to be more than eight times as high as for monopolar electrocautery ($30.04 vs $246.95). 22 A randomised controlled trial comparing four different energy-based tissue dissection techniques for abdominoplasty calculated much higher costs for the PEAK PlasmaBlade™, with no significant differences in wound-healing complications and drainage quantity.…”
Section: Discussionmentioning
confidence: 94%
“…22 However, the same study found average overall procedural costs for the PEAK PlasmaBlade™ to be more than eight times as high as for monopolar electrocautery ($30.04 vs $246.95). 22 A randomised controlled trial comparing four different energy-based tissue dissection techniques for abdominoplasty calculated much higher costs for the PEAK PlasmaBlade™, with no significant differences in wound-healing complications and drainage quantity. 23 In contrast, Kypta et al found significantly reduced procedure times and hospital stays for the PEAK PlasmaBlade™, as well as a cost savings of approximately €120 per patient in a retrospective analysis of techniques used for cardiovascular device replacement.…”
Section: Discussionmentioning
confidence: 94%
“…This has been done in other studies showing a large variation in direct costs between different health care facilities, depending on numerous factors [12, 25]. In one study, the cost of using radiofrequency was 8 times higher than for monopolar cautery in pediatric adenotonsillectomy [26]. Also, coblation tonsillectomy has been shown to be considerably more expensive than electrocautery due to high costs for disposables, despite a shorter time in the operating theatre [27] .This important aspect needs further analysis, especially since tonsillotomy is usually performed with more expensive surgical methods than tonsillectomy [28].…”
Section: Discussionmentioning
confidence: 95%
“…Use of low-temperature pulsed radiofrequency energy has been developed for efficient tissue dissection with minimal thermal damage. [4][5][6][7][8][9] The goal was to compare pain scores during the 14-day postoperative period. To our knowledge, there are no known published prospective clinical trials of the PEAK PlasmaBlade on pain outcomes in pediatric patients undergoing adenotonsillectomy.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there are no known published prospective clinical trials of the PEAK PlasmaBlade on pain outcomes in pediatric patients undergoing adenotonsillectomy. 9,10 Patients and Methods…”
Section: Introductionmentioning
confidence: 99%